SEM and EDS comparative studies about the homogeneity of some cements used for luting of posts - Gina Paunita Grecu; Doina Lucia Ghergic; Raluca Monica Comaneanu; Claudia Florina Bogdan-Andreescu; Cherana Gioga; Irina Maria Gheorghiu; Anna Maria Pangica; Paula Perlea; Mihail Tarcolea (Amaltea Medical Publishing House, 2023)
Objectives. The aim of the study was to evaluate comparatively by scanning electron microscope (SEM) and energy dispersive spectrophotometry (EDS) the physical and chemical homogeneity of some luting materials used for cementation of three types of posts. Materials and method. We selected 12 irretrievable monoradicular teeth extracted in our dental offices. After extraction, all teeth were prepared for cementation with 4 different cements (NANOCORE DUAL, CEMBEST, PANAVIA SA and CEMENT-ONE) of three types of posts: prefabricated titanium post, FibreKleer 4x fiberglass post (Pentron) and post cast from NiCrMo alloy. Afterwards, the samples were embedded in resin and prepared metallographically for examination with the Phenom ProX scanning electron microscope equipped with an energy dispersive spectrophotometer with X Rays. Results. SEM studies provide valuable ultrastructural information regarding the degree of filling with luting materials. The four studied cements do not present an inhomogeneous composition in the EDS analysis, not having significantly increased values between the 2 analyzed points for each of the 12 samples taken in the study. Conclusions. Among the four luting materials studied comparatively, PANAVIA SA seems to best fill the existing spaces between posts and the limits of dental preparations, being closely followed by CEMENT-One and CEMBEST. In last place is NANOCORE DUAL, which presents discontinuities in the mass of material and at the border with the preparations.